ASSISTANCE IN SOCIALIZATION OF THE TAPAK DARA PLANT AS A MOSQUITO REPELLENT - Rochmat, Rustam Aji; Suriani, Suriani; Lusiani, Dewi; Aji, Sherly Ratih Frichesyarius Santi; Ayuningtyas, Roro Aji; Fahlevi, Reza; Wijaya, Yohannes; Andini, Indah Fitri (LP2M STP Mataram, 2024)
During the transition season, there are lots of mosquitoes around, some of which contain the dengue virus which can transmit dengue hemorrhagic fever (DHF) which is transmitted through the bite of the Aedesaegypti mosquito. Students understand and are able to explain the purpose of community service activities. The initial survey was carried out at 09.00 – 10.00 WIT, Saturday 20 July February 2024. Providing socialization there were 4 pots of periwinkle plants in class VI.B and 18 pots of periwinkle plants in the yard of class VI B.SDN.07 Rejang Lebong. The school's suggestion is to cultivate it by planting more periwinkles indoors (in the classroom) and outdoors in the environment outside the school classroom as a mosquito repellent.